A magnetic fluorinated multi-walled carbon nanotubes-based QuEChERS method for organophosphorus pesticide residues analysis in Lycium ruthenicum Murr. (15th February 2021) - Wang, Jun; Duan, Hui-Ling; Fan, Li; Zhang, Jing; Zhang, Zhi-Qi
Highlights: Magnetic fluorinated MWCNTs were first designed and prepared. A modified QuEChERS method was developed with prepared materials as clean-up agent. The interfering substances in Lycium ruthenicum Murr. could be effectively removed. The clean-up performance is superior than the combination of PSA and C18. Abstract: In order to meet the requirements of pesticide residues' detection in complex matrix samples, the magnetic fluorinated multi-wall carbon nanotubes (M-F-MWCNTs) were prepared and applied as new QuEChERS clean-up materials. Combined with GC–MS, an improved QuEChERS method was successfully developed for the detection of organophosphorus pesticide residues. The results showed that the M-F-MWCNTs could effectively remove the interfering substances in Lycium ruthenicum Murr. ( L. ruthenicum ) samples. The recoveries of 10 tested targets were 74.9% to 113.5% with the relative standard deviations (RSDs) of 3.9–14.7%. The experiment results pointed out that the M-F-MWCNTs were qualified as QuEChERS clean-up materials and expected to be applied to other complex matrix samples and pesticide targets.